A scoping review of the additive manufacturing of mandibular implants - Winarso, Rochmad; Ismail, Rifky; Anggoro, Paulus Wisnu; Jamari, Jamari; Bayuseno, Athanasius Priharyoto (Frontiers in Mechanical Engineering, 2023)
Bone disease and fractures are among the health issues that are becoming more prevalent year after year. A mandibular disorder is caused by an accident or disease to the largest and strongest bone in the human face. Because the natural healing process of mandibular bones takes a long time, a bone grafting procedure is used to speed up the patient’s recovery. Due to the limitations of bone grafting processes such as autographs, allographs, and xenografts, bone replacement is being developed using biomaterials via 3D printing. The purpose of the review was to evaluate research on the use of 3D printing in the replacement of mandible bones. The search algorithm found as many as 2,941 articles at the start of the search and 123 articles after initial selection. Up to February 2022, the Scopus electronic database was used to conduct the literature search. This research includes publications that employ 3D printers, additive manufacturing, or finite element analysis to build or analyze mandibular implants. Paper topics in engineering, materials science, biochemistry, genetics, molecular biology, medicine, dentistry, chemical engineering, and computer science are included in this study. Papers in physics, astronomy, and energy, book chapter document types, papers reviews, and documents in languages other than English were excluded from this study. After an initial screening that included the year, publication stage, source type, and language, as many as 70 articles were obtained, and after filtering titles and abstracts obtained 55 articles. After the full-text selection was obtained, 32 articles were included in this review. Some articles were unacceptable because the topics discussed were unrelated to mandibular bone scaffolds. As a result, the field of additive manufacturing for the repair and reconstruction of mandibular defects necessitates the development of novel tools and methodologies. A customized biological scaffold can be created using an appropriate 3D printing process based on the characteristics of various mandibular defects, allowing it to be perfectly matched to the defect region and reducing stress, thereby improving the scaffold’s healing function.